Novel design of Fe-Cu alloy coated cellulose nanocrystals with strong antibacterial ability and efficient Pb2+ removal. (15th April 2020) - Chen, Lumin; Yu, Houyong; Deutschman, Christopher; Yang, Ting; Tam, Kam Chiu
Graphical abstract: Highlights: Fe-Cu@CNC composites were prepared by simple oxidation-reduction reaction. The composites have high antibacterial ratio of 95.9 %–99.9 % against bacteria. The composites have excellent Pb (II) adsorption ability of 93.98 % removal ratio. The composites can retain 80.41 % of original removal efficiency after six cycles. Abstract: We report a facile method to prepare a novel composite based on Fe-Cu alloy decorated cellulose nanocrystals (Fe-Cu@CNC) via simple oxidation-reduction reaction. Spherical zero-valent iron nanoparticles (NZVI) and sheet-like copper nanoparticles were serially anchored on the CNC surface, and the generated composite exhibited excellent antibacterial activities and highly efficient Pb 2+ removal. The composites had high antibacterial ratios of 95.9 %–99.9 %, because superoxide radicals can cause irreversible damage to the bacteria, eventually leading to apoptosis and bacterial death. Meanwhile, the Fe-Cu@CNC composite showed quick Pb 2+ ion removal, reaching a 70.76 % removal within 5 min, a total removal of 93.98 % after 1 h, and excellent reusability (retaining removal efficiency of 80.41 % after six cycles). The adsorption kinetics demonstrated that the adsorption behavior can be described by pseudo-second-order kinetic model (R 2 >0.99). This study offers a new strategy to prepare a promising composite with advanced antibacterial and heavy metal removal properties for wastewater treatment.